High-specific-volume barium titanate-based ceramic material, preparation method thereof and capacitor
By developing high-specific capacitance barium titanate-based ceramic materials, using Ca, Bi, Mg and Zr elements to optimize dielectric performance, the problem of insufficient energy storage performance of existing ceramic capacitors at high temperatures is solved, and no cooling is required in high temperature environments The stable energy storage performance of the device is suitable for applications such as electric vehicles and photovoltaic power generation.
Patent Information
- Application Number
- CN202411547389.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
Existing ceramic capacitors cannot meet the high energy storage performance and high operating temperature requirements for applications such as electric vehicles and photovoltaic power generation in high temperature environments, resulting in the need of additional cooling devices to ensure the normal operation of the system.
Develop a high specific capacitance barium titanate-based ceramic material with the chemical formula of (1-x)(Ba0.8Ca0.2)TiO3-xBi(Mg0.5Zr0.5)O3 by introducing Ca, Bi, Mg and Zr elements , optimize the dielectric properties and temperature stability of ceramic materials to ensure stable energy storage performance at high temperatures.
The ceramic material exhibits high energy density and energy efficiency under high temperature environment (>150°C), has excellent energy storage temperature stability and cycle stability, and can ensure electric vehicles without the need for additional heat dissipation devices. and the normal operation of circuit modules in photovoltaic power generation.
Smart Images

Figure CN119430908A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and specifically relates to a high-specific-capacity barium titanate-based ceramic material and a preparation method thereof, and particularly relates to a capacitor. Background Art
[0002] Capacitors can be divided into electrolytic capacitors, film capacitors, ceramic capacitors, supercapacitors, etc. according to the different dielectric materials. For high-temperature applications, such as inverter modules in electric vehicles, the operating temperature is generally above 150 degrees, and electrolytic capacitors and supercapacitors cannot work properly at this temperature. Since the dielectric layer of film capacitors is a polymer macromolecular material, it has problems with softening and melting at high temperatures, so it is not suitable for high-temperature environments. Although ceramic capacitors have the best high-temperature energy storage performance, the current maximum operating temperature of commercial ceramic capacitors is 125 degrees, which still cannot meet the requirements of high-temperature applications. The current solution is generally to design additional cooling devices to cool the circuit modules and ensure the normal operation of the modules.
[0003] The addition of additional cooling devices will inevitably increase the volume and weight of the entire system, taking up space for the system's "effective materials". For example, without cooling devices, electric vehicles can add more battery packs to improve their range.
[0004] Therefore, the development of ceramic capacitors with both high energy storage performance and high operating temperature is expected to realize a system without cooling devices and improve the performance of the entire system. Summary of the invention
[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems: In the related art, the materials for preparing capacitors cannot meet the requirements of high energy storage performance and high operating temperature for applications such as electric vehicles and photovoltaic power generation. Therefore, it is necessary to study and improve the ceramic materials for preparing capacitors.
[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention proposes a high specific volume barium titanate-based ceramic material, which has stable energy storage performance at high temperatures (>150°C), and can ensure that circuit modules working at high temperatures in electric vehicles and photovoltaic power generation can work normally without the need to add additional heat dissipation devices.
[0007] The barium titanate-based ceramic material of the embodiment of the present invention has the chemical formula: (1-x)(Ba 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3, where 0.3≤x≤0.4.
[0008] The advantages and technical effects of the barium titanate-based ceramic material of the embodiment of the present invention are as follows: 1. In the ceramic material of the embodiment of the present invention, barium titanate is used as the matrix material. By introducing the Ca element, the dielectric loss can be reduced and the dielectric constant can be improved. At the same time, Bi, Mg, and Zr elements are introduced. Bi can improve the dielectric constant, Mg can improve the breakdown strength and insulation resistance, and Zr can improve the breakdown strength, insulation resistance, and temperature stability of the dielectric constant; 2. In the embodiment of the present invention, the chemical formula (1-x) (Ba) of the ceramic material is controlled by strictly controlling the content of each element. 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3, each element gives full play to its maximum advantage and synergistic effect, which can make the ceramic material have higher energy density and energy efficiency at high temperature (>150℃), and at the same time, the ceramic material has excellent energy storage temperature stability under variable temperature environment, and excellent energy storage cycle stability under high temperature environment. The excellent energy storage performance of the ceramic material in the embodiment of the present invention can ensure that the circuit modules working at high temperature in electric vehicles and photovoltaic power generation can work normally without the need to add additional heat dissipation devices.
[0009] In some embodiments, the barium titanate-based ceramic material has an energy storage figure of merit of 21-29 at 25° C. and 250 kV / cm electric field, wherein energy storage figure of merit=energy density / (1-energy efficiency).
[0010] In some embodiments, the barium titanate-based ceramic material has an energy efficiency of not less than 90% under an electric field of 300 kV / cm-450 kV / cm and a temperature range of -50°C to 250°C.
[0011] The embodiment of the present invention also provides a method for preparing a high specific volume barium titanate-based ceramic material, comprising the following steps:
[0012] (1) BaCO3, CaCO3, Bi2O3, TiO2, MgO and ZrO2 are mixed according to the designed ratio and subjected to the first ball milling treatment, and then dried to obtain a powder:
[0013] (2) pre-calcining the powder obtained in step (1) to obtain pre-calcined powder;
[0014] (3) subjecting the pre-sintered powder obtained in step (2) to a second ball milling process, and obtaining a ceramic powder after drying;
[0015] (4) pressing the ceramic powder obtained in step (3) into tablets, and subjecting the tablets to cold isostatic pressing to obtain a ceramic embryo;
[0016] (5) subjecting the ceramic body obtained in step (4) to a binder removal treatment;
[0017] (6) The upper surface and the lower surface of the ceramic body obtained after the binder removal treatment in step (5) are respectively covered with the pre-fired powder obtained in step (2), and the barium titanate-based ceramic material is obtained after sintering.
[0018] Advantages and technical effects brought by the preparation method of barium titanate-based ceramic material in the embodiment of the present invention: 1. In the embodiment of the present invention, a high-temperature solid-phase method is adopted to synthesize ceramic material, and the process operation is simple and easy to apply; 2. In the embodiment of the present invention, pre-fired powder is respectively covered on the upper and lower surfaces of the ceramic body after debinding treatment, which is beneficial to reduce the volatilization of elements in the ceramic body; 3. The ceramic material prepared by the method of the embodiment of the present invention has stable energy storage performance at high temperature (>150°C), which can ensure that the circuit modules working at high temperature in electric vehicles and photovoltaic power generation can work normally without the need to add additional heat dissipation devices.
[0019] In some embodiments, in step (1), the first ball milling treatment time is 6-12 hours.
[0020] In some embodiments, in step (2), the temperature of the pre-sintering treatment is 800-900° C., the time is 2-8 hours, and preferably, the heating rate is 3-10° C. / min.
[0021] In some embodiments, in step (3), the second ball milling treatment includes: ball milling the pre-burned powder for 20 to 24 hours, then adding a binder, and continuing the ball milling treatment for 1 to 3 hours. Preferably, the binder includes RHOPLEX HA-8, and the amount of the binder added is 0.1 to 0.5% of the mass of the pre-burned powder.
[0022] In some embodiments, in step (4), the tabletting pressure is 50-100 MPa, the cold isostatic pressing pressure is 200-300 MPa, and the cold isostatic pressing processing time is 1-10 minutes.
[0023] In some embodiments, in step (5), the debinding treatment includes heating the ceramic body to 500-700° C. and keeping the temperature for 1-4 hours. Preferably, the heating rate is 0.5-3° C. / min.
[0024] In some embodiments, in step (6), the sintering temperature is 1100-1350° C., the sintering time is 1-4 hours, and preferably, the heating rate is 3-7° C. / min.
[0025] The embodiment of the present invention also provides an application of a barium titanate-based ceramic material in an electric vehicle or a photovoltaic power station. The barium titanate-based ceramic material of the embodiment of the present invention has excellent energy storage stability in a high temperature environment, and can achieve stable operation of the circuit module in the electric vehicle or photovoltaic power station in a high temperature environment without adding an additional heat dissipation device.
[0026] The embodiment of the present invention further provides a capacitor, which is made of the high specific capacity barium titanate-based ceramic material of the embodiment of the present invention. The capacitor of the embodiment of the present invention, which is made of the ceramic material of the embodiment of the present invention, has all the advantages that the ceramic material of the embodiment of the present invention can bring, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a test diagram of the variable temperature energy storage performance of the ceramic material prepared in Example 1;
[0028] Figure 2 This is a test diagram of the cycle performance of the ceramic material prepared in Example 1 under a high temperature environment;
[0029] Figure 3 This is a test diagram of the variable temperature energy storage performance of the ceramic material prepared in Example 2;
[0030] Figure 4 This is a test diagram of the cycle performance of the ceramic material prepared in Example 2 under a high temperature environment;
[0031] Figure 5 The dielectric constant of the ceramic materials prepared in Example 1, Example 2 and Comparative Example 3 varies with temperature;
[0032] Figure 6 The dielectric loss curves of the ceramic materials prepared in Example 1, Example 2 and Comparative Example 3 are plotted as a function of temperature. DETAILED DESCRIPTION
[0033] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0034] The barium titanate-based ceramic material of the embodiment of the present invention has the chemical formula: (1-x)(Ba 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3, where 0.3≤x≤0.4.
[0035] In the barium titanate-based ceramic material of the embodiment of the present invention, barium titanate is used as the matrix material. By introducing the Ca element, the dielectric loss can be reduced and the dielectric constant can be improved. At the same time, Bi, Mg, and Zr elements are introduced. Bi can improve the dielectric constant, Mg can improve the breakdown strength and insulation resistance, and Zr can improve the breakdown strength, insulation resistance, and temperature stability of the dielectric constant. In the embodiment of the present invention, the chemical formula (1-x) (Ba) of the ceramic material is controlled by strictly controlling the content of each element. 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3, each element gives full play to its maximum advantage and synergistic effect, which can make the ceramic material have higher energy density and energy efficiency at high temperature (>150℃), and at the same time, the ceramic material has excellent energy storage temperature stability under variable temperature environment, and excellent energy storage cycle stability under high temperature environment. The excellent energy storage performance of the ceramic material in the embodiment of the present invention can ensure that the circuit modules working at high temperature in electric vehicles and photovoltaic power generation can work normally without the need to add additional heat dissipation devices.
[0036] In some embodiments, the energy storage merit of the barium titanate-based ceramic material at 25°C and 250 kV / cm electric field is 21-29, wherein energy storage merit=energy density / (1-energy efficiency). In the embodiments of the present invention, the energy storage performance of the ceramic material is evaluated by using a set parameter energy storage merit. The larger the value, the higher the energy density and energy efficiency of the ceramic material, and the better the energy storage performance.
[0037] In some embodiments, the barium titanate-based ceramic material has an energy efficiency of not less than 90% under an electric field of 300 kV / cm-450 kV / cm and in a temperature range of -50°C to 250°C. The ceramic material of the embodiment of the present invention has excellent temperature stability, and the energy efficiency is not less than 90% in a wide temperature range.
[0038] The present invention also provides a method for preparing a barium titanate-based ceramic material, comprising the following steps:
[0039] (1) BaCO3, CaCO3, Bi2O3, TiO2, MgO and ZrO2 are mixed according to the designed ratio and subjected to the first ball milling treatment, and then dried to obtain a powder:
[0040] (2) pre-calcining the powder obtained in step (1) to obtain pre-calcined powder;
[0041] (3) subjecting the pre-sintered powder obtained in step (2) to a second ball milling process, and obtaining a ceramic powder after drying;
[0042] (4) pressing the ceramic powder obtained in step (3) into tablets, and subjecting the tablets to cold isostatic pressing to obtain a ceramic embryo;
[0043] (5) subjecting the ceramic body obtained in step (4) to a binder removal treatment;
[0044] (6) The upper surface and the lower surface of the ceramic body obtained after the binder removal treatment in step (5) are respectively covered with the pre-fired powder obtained in step (2), and the barium titanate-based ceramic material is obtained after sintering.
[0045] In the preparation method of the barium titanate-based ceramic material in the embodiment of the present invention, a high-temperature solid-phase method is used to synthesize the ceramic material. The process operation is simple and easy to apply. In addition, pre-fired powder is respectively covered on the upper and lower surfaces of the ceramic body after debinding treatment, which is beneficial to reduce the volatilization of elements in the ceramic body. The ceramic material prepared by the method of the embodiment of the present invention has stable energy storage performance at high temperature (>150°C), which can ensure that the circuit modules working at high temperature in electric vehicles and photovoltaic power generation can work normally without the need to add additional heat dissipation devices.
[0046] In some embodiments, in step (1), the first ball milling treatment time is 6-12 hours.
[0047] In some embodiments, in step (2), the temperature of the pre-sintering treatment is 800-900° C., the time is 2-8 hours, and preferably, the heating rate is 3-10° C. / min.
[0048] In some embodiments, in step (3), the second ball milling process comprises: ball milling the pre-sintered powder for 20 to 24 hours, then adding a binder, and continuing the ball milling process for 1 to 3 hours. Preferably, the binder comprises RHOPLEX HA-8, and the amount of the binder added is 0.1 to 0.5% of the mass of the pre-sintered powder. In the embodiment of the present invention, the pre-sintered powder is subjected to a secondary ball milling process, which can further improve the subsequent sintering activity while reducing the particle size.
[0049] In some embodiments, in step (4), the tabletting pressure is 50-100 MPa, the cold isostatic pressing pressure is 200-300 MPa, and the cold isostatic pressing treatment time is 1-10 minutes. In the embodiment of the present invention, the ceramic powder is tableted and cold isostatically pressed to further improve the density of the ceramic body.
[0050] In some embodiments, in step (5), the debinding treatment includes heating the ceramic body to 500-700° C. and keeping the temperature for 1-4 hours. Preferably, the heating rate is 0.5-3° C. / min.
[0051] In some embodiments, in step (6), the sintering temperature is 1100-1350° C., the sintering time is 1-4 hours, and preferably, the heating rate is 3-7° C. / min.
[0052] The present invention is described in detail below with reference to embodiments.
[0053] Example 1
[0054] (1) BaCO3, CaCO3, Bi2O3, TiO2, MgO, and ZrO2 are used as raw materials according to the chemical formula 0.7 (Ba 0.8 Ca 0.2 )TiO3-0.3Bi(Mg 0.5 Zr 0.5 )O3(i.e.(1-x)(Ba 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3 in which x=0.3) is mixed in a stoichiometric ratio to obtain a raw material mixture, which is subjected to a first ball milling treatment for 10 hours and dried to obtain a powder:
[0055] (2) heating the powder to 850° C. at a rate of 5° C. / min and calcining for 3 h to obtain pre-calcined powder;
[0056] (3) The pre-sintered powder was subjected to a second ball milling treatment, first ball milling for 21 hours, then a binder RHOPLEX HA-8 was added, ball milling was continued for 1.5 hours, and then dried to obtain a ceramic powder;
[0057] (4) After pressing the ceramic powder into a disc at 80 MPa, cold isostatic pressing is performed at 220 MPa for 5 minutes to increase the density of the ceramic body, thereby obtaining a ceramic body;
[0058] (5) heating the ceramic body to 600° C. at a rate of 1° C. / min, keeping the temperature for 2 h, performing a binder removal treatment, and then cooling the ceramic body to room temperature;
[0059] (6) The upper and lower surfaces of the debinding ceramic body are respectively covered with pre-fired powder of the same composition as that treated in steps (1) and (2) to reduce the volatilization of elements in the ceramic body, and then the temperature is increased to 1150° C. at 5° C. / min and sintered for 3 hours to obtain a ceramic material.
[0060] Example 2
[0061] The method is the same as that of Example 1, except that in step (1), the chemical formula 0.6 (Ba 0.8 Ca 0.2 )TiO3-0.4Bi(Mg 0.5 Zr 0.5)O3(i.e.(1-x)(Ba 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3 is prepared in the stoichiometric ratio of x=0.4).
[0062] Comparative Example 1
[0063] The method is the same as that of Example 1, except that Bi2O3, MgO and ZrO2 are not added in step (1).
[0064] Comparative Examples 2-3
[0065] The method is the same as that of Example 1, except that the chemical formula of the prepared ceramic material is different, as shown in Table 1.
[0066] The energy storage performance of the ceramic materials prepared in the embodiments and comparative examples was tested. The test results are shown in Table 1 and Figure 1 and Figure 2 .
[0067] Test method: Grind the ceramic sheet samples prepared in the embodiments and comparative examples to a thickness of 50 microns, clean them in acetone and ethanol in turn, and dry them. Place a stainless steel mask on the ceramic sheet, set a plurality of small holes with a diameter of 1 mm on the mask, send the ceramic sheet and the mask into an ion plating instrument to sputter a gold film with a thickness of about 100 nanometers. After the sputtering is completed, remove the mask, and leave a gold electrode with a diameter of 1 mm on the surface of the ceramic sheet. Turn the ceramic sheet over and sputter the gold electrode again so that the gold electrode covers the entire ceramic surface. Use a ferroelectric tester to test the hysteresis loop and calculate the energy storage density. For the variable temperature test, place the ceramic sheet on a heating table and test it with a ferroelectric tester.
[0068] Energy density and energy efficiency calculation: Based on the data of the hysteresis loop, the area enclosed by the charging curve and the vertical axis (polarization intensity axis) is calculated by the integration method and recorded as the total energy density; the area enclosed by the discharge curve and the vertical axis is calculated and recorded as the releasable energy density (i.e., "energy density" in Table 1). The ratio of the releasable energy density to the total energy density is calculated to obtain the energy efficiency.
[0069] Table 1
[0070]
[0071] Note: 1. The energy density and energy efficiency in Table 1 are test data at 25°C and 250 kV / cm electric field;
[0072] 2. Energy storage figure of merit = energy density / (1-energy efficiency).
[0073] As can be seen from Table 1, in the present embodiment, Ca, Bi, Mg and Zr are introduced into the barium titanate substrate to prepare a barium titanate substrate having the chemical formula (1-x)(Ba 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3 ceramic material, and control x = 0.3-0.4, so that the ceramic material has stable energy storage performance at high temperature (>150℃), and the energy storage figure of merit under 250kV / cm electric field can be as high as 28.2. It can ensure that the circuit modules working at high temperature in electric vehicles and photovoltaic power generation can work normally without adding additional heat dissipation devices.
[0074] Figure 1 The hysteresis loop of the ceramic material of Example 1 under the electric field of 450 kV / cm in the range of -50 to 260 ° C is shown in FIG. Figure 1 It can be seen that the energy density of the ceramic material of Example 1 is about 4.55-5.0 J / cm in the temperature range of -50 to 260°C. 3 The change does not exceed 9%, and the energy efficiency is always maintained above 90%, indicating that the ceramic material of Example 1 has excellent energy storage temperature stability.
[0075] Figure 2 The hysteresis loop of the ceramic material of Example 1 under 200°C temperature and 450kV / cm electric field for multiple cycles is shown in FIG. Figure 2 It can be seen that after the ceramic material of Example 1 is cycled 1 million times, the energy density of the ceramic material is basically maintained at 4.6-4.7 J / cm from the initial to the 1 millionth cycle. 3 The energy efficiency is basically maintained between 93-95%, and the energy storage performance of the ceramic material remains almost unchanged, indicating that the ceramic material of Example 1 has excellent cycle reliability at high temperature.
[0076] Figure 3 The hysteresis loop of the ceramic material of Example 2 under the electric field of 300 kV / cm in the range of -50 to 250 ° C is shown in FIG. Figure 3 It can be seen that the energy density of the ceramic material of Example 2 is about 3.01-3.36 J / cm in the temperature range of -50 to 250 °C. 3 The change is about 10%, and the energy efficiency is always maintained above 90%, indicating that the ceramic material of Example 2 has excellent energy storage temperature stability.
[0077] Figure 4 The hysteresis loop of the ceramic material of Example 2 was repeatedly cycled at 200°C and 300 kV / cm electric field. Figure 4It can be seen that after the ceramic material of Example 2 is cycled 1 million times, the energy density of the ceramic material is basically maintained at 3.05-3.15 J / cm from the initial to the 1 millionth cycle. 3 The energy efficiency is basically maintained between 92.5% and 96%, and the energy storage performance of the ceramic material remains almost unchanged, indicating that the ceramic material of Example 2 has excellent cycle reliability at high temperatures.
[0078] In Comparative Example 1, Bi, Mg, and Zr were not introduced. Due to the strong ferroelectricity of the sample, its energy density was very low, only 0.89 J / cm 3 , the energy efficiency is only 44.2%, so the energy storage figure of merit can only reach 1.6, and the energy storage performance is very poor.
[0079] In Comparative Example 2, the chemical formula of the ceramic material is 0.9(Ba 0.8 Ca 0.2 )TiO3-0.1Bi(Mg 0.5 Zr 0.5 )O3, although the energy density is higher than that of Examples 1 and 2, due to the insufficient contents of Bi, Mg and Zr, the sample still retains some ferroelectricity, and its energy efficiency is very low, only 75.8%, and the final energy storage figure of merit can only reach 7.2, which cannot achieve a high energy density and a high energy efficiency at the same time.
[0080] In Comparative Example 3, the chemical formula of the ceramic material is 0.8(Ba 0.8 Ca 0.2 )TiO3-0.2Bi(Mg 0.5 Zr 0.5 )O3, although its energy storage merit at room temperature is basically the same as that of Example 2, but by testing the dielectric properties of the three materials prepared in Example 1, Example 2 and Comparative Example 3, it is found that Figure 5 It can be seen that the dielectric constant of the ceramic material with x=0.2 obtained in Example 3 decreases rapidly above room temperature, indicating that the dielectric properties of the ceramic material in Example 3 are unstable in the high temperature region, which is not conducive to obtaining stable energy storage performance. Figure 6 It can be seen that in the high temperature region greater than 100°C, especially in the high temperature region greater than 200°C, the dielectric loss of the ceramic material prepared in Comparative Example 3 is higher than that of the ceramic materials prepared in Examples 1 and 2. Since ceramic materials must withstand high temperature and high voltage at the same time under high temperature energy storage working conditions, the energy storage stability of the ceramic material prepared in Comparative Example 2 at high temperature will be significantly inferior to that of the ceramic materials in Examples 1 and 2.
[0081] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0082] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A high specific volume barium titanate-based ceramic material, characterized in that: The chemical formula of the high specific volume barium titanate-based ceramic material is: (1-x)(Ba 0.8 Ca 0.2 )TiO3-xBi(Mg 0.5 Zr 0.5 )O3, where 0.3≤x≤0.
4.
2. The high specific volume barium titanate-based ceramic material according to claim 1, characterized in that: The energy storage merit of the barium titanate-based ceramic material at 25° C. and 250 kV / cm electric field is 21-29, wherein energy storage merit=energy density / (1-energy efficiency).
3. The high specific volume barium titanate-based ceramic material according to claim 1, characterized in that: The energy efficiency of the barium titanate-based ceramic material is not less than 90% under an electric field of 300 kV / cm-450 kV / cm and within a temperature range of -50°C to 250°C.
4. A method for preparing a high specific volume barium titanate-based ceramic material according to any one of claims 1 to 3, characterized in that: The steps include: (1) BaCO3, CaCO3, Bi2O3, TiO2, MgO and ZrO2 are mixed according to the designed ratio and subjected to the first ball milling treatment, and then dried to obtain a powder: (2) pre-calcining the powder obtained in step (1) to obtain pre-calcined powder; (3) subjecting the pre-sintered powder obtained in step (2) to a second ball milling process, and obtaining a ceramic powder after drying; (4) pressing the ceramic powder obtained in step (3) into tablets, and subjecting the tablets to cold isostatic pressing to obtain a ceramic embryo; (5) subjecting the ceramic body obtained in step (4) to a binder removal treatment; (6) The upper surface and the lower surface of the ceramic body obtained after the binder removal treatment in step (5) are respectively covered with the pre-fired powder obtained in step (2), and the barium titanate-based ceramic material is obtained after sintering.
5. The method for preparing a high specific volume barium titanate-based ceramic material according to claim 4, characterized in that: In the step (1), the first ball milling treatment time is 6-12 hours; And / or, in the step (2), the temperature of the pre-sintering treatment is 800-900° C., the time is 2-8 hours, and preferably, the heating rate is 3-10° C. / min.
6. The method for preparing a high specific volume barium titanate-based ceramic material according to claim 4, characterized in that: In the step (3), the second ball milling treatment comprises: ball milling the pre-sintered powder for 20 to 24 hours, then adding a binder, and continuing the ball milling treatment for 1 to 3 hours. Preferably, the binder comprises RHOPLEX HA-8, and the amount of the binder added is 0.1 to 0.5% of the mass of the pre-sintered powder.
7. The method for preparing a high specific volume barium titanate-based ceramic material according to claim 4, characterized in that: In the step (4), the tabletting pressure is 50 to 100 MPa, the cold isostatic pressing pressure is 200 to 300 MPa, and the cold isostatic pressing processing time is 1 to 10 minutes.
8. The method for preparing a high specific volume barium titanate-based ceramic material according to claim 4, characterized in that: In the step (5), the debinding treatment includes heating the ceramic body to 500-700° C. and keeping the temperature for 1-4 hours. Preferably, the heating rate is 0.5-3° C. / min. And / or, in the step (6), the sintering temperature is 1100-1350° C., the sintering time is 1-4 hours, and preferably, the heating rate is 3-7° C. / min.
9. Use of the high specific volume barium titanate-based ceramic material according to any one of claims 1 to 3 or the high specific volume barium titanate-based ceramic material prepared by the preparation method according to any one of claims 4 to 8 in electric vehicles or photovoltaic power stations.
10. A capacitor, characterized in that: The invention is made of the high specific volume barium titanate-based ceramic material according to any one of claims 1 to 3 or the high specific volume barium titanate-based ceramic material prepared by the preparation method according to any one of claims 4 to 8.
Citation Information
Patent Citations
High-energy-storage barium titanate dielectric material and preparation method thereof
CN109133915A